Embedding the water-energy food-environment (WEFE) nexus in university curriculum: the Tribhuvan University experience - Koirala, Sanju; Khadka, Manohara; Pandey, V. P. (International Water Management Institute, 2025)
The technical brief highlights the institutionalization of the Water–Energy–Food–Environment (WEFE) nexus course at Tribhuvan University, Nepal, through collaboration with the WEFE NEXUS Policy’s Area of Work (AoW4) under CGIAR’s Policy Innovations Science Program. It underscores the need to move beyond siloed natural resource management toward integrated, interdisciplinary approaches that address climate change, sustainability, and the Sustainable Development Goals (SDGs). The curriculum was developed with participatory input from experts. The graduate-level course was piloted in 2024 and officially adopted in 2025. Parallel efforts expanded the course to the Institute of Forestry, supported by Training of Trainers programs. Future directions emphasize faculty capacity-building, student research support, and the integration of local case studies for practical learning.